The Analysis of Metaphors of Modality in The Book Into the Magic Shop: A Neurosurgeon Quest to Discover the Mysteries of the Brain and the Secrets of the Hearts by James R Doty, MD - ‘Adzra, Haniifatul; Ayendi, Ayendi (English Department, Faculty of Humanities, Andalas University, 2024)
The metaphor of modality is a language variation in the expression ofmodality. Analyzing the metaphor of modality is important to see thedegree of certainty of utterances in communication. The theory by M.A.KHalliday (1994), specifically the metaphor of modality, was applied to seethe use of the metaphor of modality in the autobiography book. This studyaimed to find the types and values of the metaphor of modality used by thewriter in the book. The method of this study was a descriptive qualitativemethod. The data collected were labeled based on the mental processelements and mood elements in the box. This research found that thereare 110 data containing metaphors of modality found in the book IntoThe Magic Shop. All of the data is categorized into types and values ofmetaphors of modality. The types are probability with 56 (50.91%) data,usuality 2 (1.82%) data, the type of obligation has 38 (34.55%) data, andlastly, inclination with 14 (12.73%) data. Then, the value of metaphor ofmodality found which are high with 51 (46.36%) data, median value with41 (32.27%) data, and low value with 18 (16.36%) data. The most occurredtype found in the book is the probability type of metaphor of modality, andfollowed with the most dominant value of metaphor of modality is highvalue of metaphor of modality.